Innovation strategies of German firms: The effect of competition and intellectual property protection - Olga Slivko (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
This article analyzes how the perceived effectiveness of intellectual property protection and competitive pressure affect firms' innovation strategy choices, concretely, whether to abstain from innovation, to introduce products that are known in the market but new to the firm (imitation) or to introduce market novelties (innovation). Using a sample of 1253 German firms from manufacturing and services sectors I show that the perceived effectiveness of patent protection positively affects firms' propensity to imitate and to innovate. Having a small or a medium number of competitors positively affects firms' propensity to imitate and to innovate as compared to being a monopolist or having a large number of competitors. However, this effect varies with the perceived patent protection effectiveness. If the perceived patent protection effectiveness is low or medium, both innovation and imitation are enhanced, whereas if it is high, only innovation is enhanced.
urn:nbn:de:bsz:180-madoc-329851
Keywords: C35; L13; O31; O34; 330; Innovation; imitation; competitive pressure; intellectual property protection